Examining Factors that Support Continued Use of Assistive Technology by Postsecondary Students with Disabilities - Lauren Denise Goegan; Lily Le; Brigitte P. Rioux; Lia M. Daniels (Canadian Society for Studies in Education, 2019)
Students with disabilities are attending postsecondary institutions in growing numbers. As such, disability service providers on campuses are providing more accommodations, including assistive technology (AT). AT can help students with a variety of learning needs; however, many students discontinue use despite the benefits that this technology can provide. To increase our understanding of discontinued use of AT, we collected both quantitative questionnaire data and open-ended written qualitative data. First, we examined three factors theorized to relate to continued use of AT and found that individual factors were more important than the environment or characteristics of the technology itself. Second, we investigated students' experiences with AT training and determined that the quality of the training experience and not simply attending training, was related to continued use of AT. Furthermore, we provide recommendations for individuals providing training to students. Collectively, the results provide the basis for suggestions concerning support and services offered to students utilizing AT.